TRADES, MILITIAS AND BROTHERHOODS. ECONOMIC SUCCESS AND PRESTIGE OF THE AFRO- AMERICANS IN SANTIAGO DE CHILE 1780-1820. - Contreras Cruces, Hugo (Revista de Historia Social y de las Mentalidades, 2014)
This paper studies a group of Mulattoes and other Afro Americans in Santiago de Chile, during the last years of the eighteenth and early nineteenth century, who through the practice of a craft or a retail business and institutional insertion in caste militias and fraternities began and solidified a process that, on one hand, resulted in the accumulation of goods that had a material and symbolic character , and, on the other hand, the increase of personal and social prestige increasingly led them away from the popular colonial sectors.